(untitled) (ENTHYMEMA, 2012)
In this paper, I reflect on the rise, development and reception of Italian psychoanalysis during the 1970s. The analysis of Elvio Fachinelli’s original analytical thought aims to a broad understanding of Italy’s autunno caldo (hot autumn) in political, social, and cultural terms, taking the 1968 protests as a point of departure for this investigation. Over this decade, in fact, Fachinelli’s psychoanalysis is not exclusively a clinical matter detached from the social context. Quite to the contrary, it is closely interwoven with some of the most urgent coeval concerns. As such, the analysis of Fachinelli’s work not only allows to bring to light crucial aspects of the relationship between psychoanalysis and cultural discourses in the 1970s, but it also enables to reassess -though the lens of psychoanalysis- a time of turmoil and discontent that radically transformed Italian history.